ChemInform Abstract: Recyclable Pd‐Incorporated Perovskite‐Titanate Catalysts Synthesized in Molten Salts for the Liquid‐Phase Oxidation of Alcohols with Molecular Oxygen. Issue 17 (4th April 2013) - Adilina, Indri Badria; Hara, Takayoshi; Ichikuni, Nobuyuki; Kumada, Nobuhiro; Shimazu, Shogo
Abstract A series of Pd‐incorporated titanate catalysts are synthesized by intercalation of Pd(NO3)2 into layered potassium titanate, which proceeds via a cation‐exchange reaction in molten phase.